EFEKTIVITAS MEDIA PEMBELAJARAN PAPAN DIAGRAM UNTUK MENINGKATKAN 4C PADA MATA PELAJARAN MATEMATIKA SISWA KELAS 4 SD NEGERI 171 TANJUNG JABUNG BARAT - Safinatun Najah; Barokah Isdaryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of diagram board learning media in improving 21st-century skills (4C), namely Critical Thinking, Communication, Collaboration, and Creativity, as well as students’ learning outcomes in Mathematics. This research employed a quantitative approach with a quasi-experimental method using the Nonequivalent Control Group Design. The research subjects were all fourth-grade students of SDN 171 Tanjung Jabung Barat in the 2025/2026 academic year, totaling 36 students, divided into an experimental class and a control class. Data were collected through tests (pretest and posttest), observations, and documentation. Data analysis was conducted using descriptive statistics and inferential statistics, including normality tests, homogeneity tests, and independent sample t-tests. The results showed that the average posttest scores of learning outcomes and 4C skills in the experimental class were higher than those in the control class. Statistical analysis indicated a significance value of 0.000 < 0.05, which means there was a significant difference between the two classes. Therefore, it can be concluded that the use of diagram board learning media is effective in improving students’ 4C skills and learning outcomes. This media creates a more interactive, visual, and meaningful learning environment, encouraging students to actively think critically, communicate, collaborate, and create during Mathematics learning activities.